Probabilistic traffic load modelling for highway bridges - O'Connor, Alan J. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2001)
Live load models prescribed by codes for the design and assessment of highway bridges have traditionally been based on conservative subjective assumptions regarding maximum lifetime load. Modern bridge design codes have attempted to move towards a more rational statistical approach in deriving their loading models.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin